Contract law in England and Wales - Fisher, James C. (Kluwer Law International, 2018)
Derived from the renowned multi-volume 'International Encyclopaedia of Laws', this practical analysis of the law of contracts in England and Wales covers every aspect of the subject -- definition and classification of contracts, contractual liability, relation to the law of property, good faith, burden of proof, defects, penalty clauses, arbitration clauses, remedies in case of non-performance, damages, power of attorney, and much more. Lawyers who handle transnational contracts will appreciate the explanation of fundamental differences in terminology, application, and procedure from one legal system to another, as well as the international aspects of contract law. Throughout the book, the treatment emphasizes drafting considerations.